METAFORA-METAFORA CINTA DALAM SAKINAH BERSAMAMU KARYA ASMA NADIA - Kurniati, Ai (SUAR BETANG, 2019)
AbstractAsma Nadia is known as a very productive Indonesian woman writer. It is said to be productive because within ten years it has produced more than fifty books. The distinctive style of language, especially the metaphor of the author Asma Nadia in her book Sakinah Bersamamu is a metaphor of love in the quote of these beautiful wisdom words which will be used as data in this paper. This paper aims to describe the metaphors of love in Sakinah Bersamamu by Asma Nadia. The method used is descriptive-qualitative as a problem-solving procedure by describing the language style of metaphor in the quotation of Asma Nadia's wisdom words. Based on the data, there are ten quotes of Asma Nadia's loving wisdom words that utilize the matafora language style.